2019
DOI: 10.1111/jdv.15999
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Patient‐Oriented SCORing for Atopic Dermatitis tool for black skin

Abstract: Background SCORing for Atopic Dermatitis (SCORAD) is a tool developed by the European Task Force on Atopic Dermatitis (AD) which is used by physicians to assess AD severity during consultations with their patients. Patient‐Oriented SCORAD (PO‐SCORAD) is a self‐assessment tool for use by patients which has been validated in a study performed in European countries. However, there is currently no adapted tool for evaluating AD severity in black skin. Objective To evaluate the performance of the version of the PO‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The SCORAD and its subcomponents (extent and intensity criteria for lesions, and subjective symptoms composed of pruritus and sleep loss scores) were calculated by the physician. The SCORAD score range is between 0 and 103 points and defines three classes of AD severity (mild if SCORAD <25, moderate if 25 ≤ SCORAD ≤50, and severe if SCORAD >50) 10 …”
Section: Assessment Of the Disease Severitymentioning
confidence: 99%
“…The SCORAD and its subcomponents (extent and intensity criteria for lesions, and subjective symptoms composed of pruritus and sleep loss scores) were calculated by the physician. The SCORAD score range is between 0 and 103 points and defines three classes of AD severity (mild if SCORAD <25, moderate if 25 ≤ SCORAD ≤50, and severe if SCORAD >50) 10 …”
Section: Assessment Of the Disease Severitymentioning
confidence: 99%
“…Furthermore, a significantly lower SCORAD at baseline was observed in infants that show outgrowth of CMA compared to infants that do not. However, the SCORAD of the majority of the infants in this study is lower than 25, corresponding to mild severity of atopic dermatitis 43 . This suggests that in this cohort, CMA does not manifest mainly through atopic symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…In this study by Faye et al. 1 including authors from seven sub‐Saharan countries, PO‐SCORAD was shown to be a validated tool for both children and adults with black skin (well correlated with SCORAD: r = 0.66, P < 0.0001). Despite the small sample size, their results suggest that it is an adapted tool for not only patients, but also dermatologists and paediatricians in the management of patients with AD in large areas where access to clinicians may be challenging.…”
Section: Patient‐reported Outcomes For Patients With Black Skin and Amentioning
confidence: 75%